Laboratory statistics : methods in chemistry and health science - Kallner, Anders (Elsevier, 2018)
Laboratory Statistics: Methods in Chemistry and Health Science, Second Edition, presents common strategies for comparing and evaluating numerical laboratory data. In particular, the text deals with the type of data and problems that laboratory scientists and students in analytical chemistry, clinical chemistry, epidemiology, and clinical research face on a daily basis. This book takes the mystery out of statistics and provides simple, hands-on instructions in the format of everyday formulas. Spreadsheet shortcuts and functions are included, along with many simple worked examples. This book is a must-have guide to applied statistics in the lab that will result in improved experimental design and analysis. This thoroughly revised second edition includes several new sections, more examples, and all formulas in Excel code.